Tracing the genus Sphaerospora: rediscovery, redescription and phylogeny of the Sphaerospora ranae (Morelle, 1929) n. comb. (Myxosporea, Sphaerosporidae), with emendation of the genus Sphaerospora - Jirků, M; Fiala, I; Modrý, D (Parasitology, 2007)
Using a combination of morphological, life-history and molecular data, we redescribe Sphaerospora ranae (Morelle, 1929) n. comb. (previously Leptotheca ranae) and emend its taxonomic status. Renal infection was recorded in 2 spp. of frogs (out of 5 amphibian spp. examined), Rana dalmatina (proposed type host) and Rana temporaria, suggesting restricted host specifity of S. ranae. We provide a description of sporogonic stages of S. ranae for the first time and suggest possible modes of its developmental cycle. Phylogenetic analysis inferred from the small-subunit ribosomal DNA revealed a close relationship of S. ranae with piscine Sphaerospora elegans (type species of the genus) and Sphaerospora truttae, forming together with distantly related Leptotheca fugu a 'Sphaerosporid clade', the basal branch to all myxosporean species. The close relationship of the 3 Sphaerospora spp. is further supported by the presence of 2 areas with extensive nucleotide insertions in the V4 region of the SSU rDNA (absent in L. fugu), morphology and life-history features. We conclude, that the spore morphology of Sphaerospora s.l., is very simple and probably represents a 'primitive', basal morphotype retained in most myxosporean lineages. Based on presented data, we propose emendation of the genus Sphaerospora using morpological, life-history and molecular features.
Keywords: protozoální DNA; spory protozoální; Host-Parasite Interactions; fylogeneze; interakce hostitele a parazita; Česká republika; Sequence Analysis, DNA; Phylogeny; Eukaryota; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; prevalence; Kidney; protozoální infekce zvířat; DNA, Protozoan; Czech Republic; Spores, Protozoan; Animals; Ranidae; Protozoan Infections, Animal; ledviny; zvířata; Prevalence; Molecular Sequence Data; DNA, Ribosomal